2014
DOI: 10.1080/07908318.2014.970192
|View full text |Cite
|
Sign up to set email alerts
|

Heritage language literacy maintenance: a study of Korean-American heritage learners

Abstract: How heritage learners successfully maintain their heritage language (HL) and literacy is a significant topic of discussion in the field of bilingual education. This study examines what factors are most closely associated with literacy competence by inspecting Korean heritage learners' language and literacy practice patterns and their literacy performance. Using language background surveys and Korean writing samples gathered from 56 Korean-English bilingual students in grades 4-12 and university undergraduates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 24 publications
2
26
0
1
Order By: Relevance
“…Park & Kitayama, 2014) and correlational designs including cross-sectional ( n = 3; e.g., McArdle, Hamagami, Bautista, et al, 2014) and longitudinal designs (Uchikoshi, 2014). Other studies used qualitative designs (interview; Leung, 2014; Wang, Capous, Koh, & Hou, 2014) or mixed methods (C. E. Kim & Pyun, 2014; A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Park & Kitayama, 2014) and correlational designs including cross-sectional ( n = 3; e.g., McArdle, Hamagami, Bautista, et al, 2014) and longitudinal designs (Uchikoshi, 2014). Other studies used qualitative designs (interview; Leung, 2014; Wang, Capous, Koh, & Hou, 2014) or mixed methods (C. E. Kim & Pyun, 2014; A.…”
Section: Resultsmentioning
confidence: 99%
“…Shen, Kim, Wang, & Chao, 2014) and applied research (e.g., evaluating the cultural adaptation of an existing parenting prevention program, Zhou, Chen, Cookston, & Wolchik, 2014). The second is on Asian American Health Disparities (Saw & Song, 2014), focusing on varied topics, such as inpatient psychiatric care (J. E. Kim, Saw, Zane, & Murphy, 2014) and quality of life among Asian American youths (Fradkin et al, 2014).…”
mentioning
confidence: 99%
“…Generally, these studies have shown that the degree, frequency, and quality of use of a minoritised language are good predictors of the kind of proficiency young speakers will develop in the language (e.g. Kim and Pyun 2014;Lü and Koda 2011). Young people's use of the language will also depend on the wider society's attitudes and reactions to the use of the language and to multilingual practices in general.…”
Section: Introductionmentioning
confidence: 99%
“…August & Shanahan, 2008;Elmeroth, 2006;Kim & Pyun, 2014;Thomas & Collier, 1997). Möjligheten att utveckla skolrelaterad litteracitet i ett språk är också beroende av formell undervisning (García, 2009).…”
Section: Modersmålsundervisningunclassified